Addressing the Global Burden of Trauma in Major Surgery - Dobson, Geoffrey P. (Frontiers in Surgery, 2015)
Despite a technically perfect procedure, surgical stress can determine the success or failure of an operation. Surgical trauma is often referred to as the “neglected step-child” of global health in terms of patient numbers, mortality, morbidity and costs. A staggering 234 million major surgeries are performed every year, and depending upon country and institution, up to 4% of patients will die before leaving hospital, up to 15% will have serious post-operative morbidity, and 5 to 15% will be readmitted within 30 days. These percentages equate to around 1000 deaths and 4000 major complications every hour, and it has been estimated that 50% may be preventable. New frontline drugs are urgently required to make major surgery safer for the patient and more predictable for the surgeon. We review the basic physiology of the stress response from neuroendocrine to genomic systems, and discuss the paucity of clinical data supporting the use of statins, beta-adrenergic blockers and calcium channel blockers. Since cardiac-related complications are the most common, particularly in the elderly, a key strategy would be to improve ventricular-arterial coupling to safeguard the endothelium and maintain tissue oxygenation. Reduced O2 supply is associated with glycocalyx shedding, decreased endothelial barrier function, fluid leakage, inflammation and coagulopathy. A healthy endothelium may prevent these “secondary hit” complications, including possibly immunosuppression. Thus the four pillars of whole body resynchronization during surgical trauma, and targets for new therapies, are: 1) the CNS, 2) the heart, 3) arterial supply and venous return functions, and 4) the endothelium. This is termed the Central-Cardio-Vascular-Endothelium (CCVE) coupling hypothesis. Since similar sterile injury cascades exist in critical illness, accidental trauma, hemorrhage, cardiac arrest, infection and burns, new drugs that improve CCVE coupling may find wide utility in civilian and military medicine.